Lithium silicate / organic lithium coated silicon-carbon composite material and preparation method thereof
By adopting the lithium silicate/organolithium coating technology with core-shell structure on silicon carbon materials, the conductivity difference and expansion problems of silicon carbon materials are solved, significantly improving the magnification and circulation performance of lithium-ion batteries, achieving more efficient Fast charge and better electrolyte compatibility.
Patent Information
- Application Number
- CN202411343449.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-20
AI Technical Summary
In high-energy density lithium-ion batteries, existing silicon carbon materials have large resistance due to the difference in electronic conductivity of the core porous carbon and low-temperature amorphous carbon, which limits the rate performance and fast charging performance of the material, and the shell cladding and electrolysis are also used. Inadequate compatibility of the liquid leads to limited improvement in the expansion and circulation performance of the material.
Lithium silicate/organolithium silicate is coated with silicon carbon composite material with core-shell structure, nitrogen-doped silicon carbon material as the core, lithium silicate is used as the intermediate layer, and organolithium compounds are deposited on the shell, through fluidized beds and mist Preparation is made by chemical method to form a uniform cladding layer to enhance conductivity and compatibility.
It significantly improves the electronic conductivity and ionic conductivity of the material, reduces expansion, improves the magnification and cycling performance, improves the first-time efficiency and fast charging performance, and has good compatibility with the electrolyte, which extends the material's Service life.
Smart Images

Figure CN119170772A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of lithium ion battery material preparation, in particular to a lithium silicate / organic lithium coated silicon-carbon composite material, and also relates to a preparation method of the lithium silicate / organic lithium coated silicon-carbon composite material. Background Art
[0002] Silicon-carbon materials are used in high-energy-density lithium-ion batteries for their high specific capacity, low full-charge expansion, and excellent cycle performance. However, due to the poor electronic conductivity of the core porous carbon and the amorphous carbon generated at low temperatures, the material has a large resistance. Therefore, in order to improve the rate performance of the material, it is necessary to modify the core porous carbon to improve the electronic conductivity of the material and the shell coating to improve the electronic or ionic conductivity of the material, thereby improving the rate and fast charging performance. For example, patent application number CN202211703892.2 discloses a doped silicon-carbon composite material and its preparation method and application. The preparation method is as follows: S1. Add nano-silicon, carboxylic acid rare earth compound, silver, and amorphous carbon to a silane coupling agent solution to obtain a doped silicon-carbon precursor material; S2. Deposit a fast ion conductor layer on its surface by atomic vapor deposition to obtain a fast ion conductor layer-coated composite material; S3. Carbonize to obtain the doped silicon-carbon composite material. Although the obtained material has an outer layer coated with a fast ion conductor to improve the material's ionic conductivity and its initial efficiency, the improvement on the material's expansion is limited, and the compatibility of the coating layer with the electrolyte is general, resulting in limited improvement in the material's rate performance. Summary of the invention
[0003] The purpose of the present invention is to overcome the above-mentioned shortcomings and provide a lithium silicate / organic lithium coated silicon-carbon composite material that can enhance the fast charging performance of silicon-carbon materials, reduce expansion, and improve rate performance and cycle performance.
[0004] The invention discloses a lithium silicate / organic lithium coated silicon carbon composite material, wherein the composite material presents a core-shell structure, wherein the core is a nitrogen-doped silicon carbon material, the middle layer is lithium silicate, and the outer shell is an organic lithium compound; according to the thickness ratio of the composite material, the core: the middle layer: the outer shell = 100: 1-5: 5-15.
[0005] A method for preparing a lithium silicate / organic lithium coated silicon-carbon composite material of the present invention comprises the following steps:
[0006] Step S1: adding porous carbon to a fluidized bed, introducing nitrogen to exhaust the air in the cavity, heating to 800-1000° C. and then introducing nitrogen source gas to obtain amino porous carbon, stopping introducing nitrogen source gas, cooling to 450-650° C., introducing silane gas at a flow rate of 100-500 SCCM for 60-600 min to obtain a silicon-carbon precursor material;
[0007] Step S2: Under an inert atmosphere, the silicon-carbon precursor material is transferred to a tube furnace, and then an oxygen mixed gas (volume ratio of oxygen: nitrogen = 1-5:10) is introduced at a flow rate of 50-200 SCCM for 30-300 minutes for light passivation to obtain a silicon dioxide-coated silicon-carbon precursor material;
[0008] Step S3: according to the mass ratio of silicon dioxide coated silicon carbon precursor material: lithium hydride = 100: 5-10, at a dew point of ≤-50°C, the silicon dioxide coated silicon carbon precursor material and lithium oxide are mixed evenly, and heated to 700-800°C for 6-12h to obtain lithium silicate coated silicon carbon material;
[0009] Step S4: adding an organic lithium compound to an organic solvent to prepare a uniform organic lithium solution with a mass concentration of 1-10wt%; depositing the organic lithium compound on the surface of the lithium silicate-coated silicon-carbon material by an atomization method at a vacuum degree of 1-100 Pa, a temperature of 50-100° C., and a deposition time of 30-300 min, and vacuum drying at 80° C. for 24 h to obtain a lithium silicate / organic lithium-coated silicon-carbon composite material.
[0010] In the above-mentioned method for preparing a lithium silicate / organic lithium coated silicon-carbon composite material, the nitrogen source gas described in step S1 is one of ammonia or dinitrogen tetrahydrogen; and the silane gas is one of monosilane or disilane.
[0011] The above-mentioned method for preparing a lithium silicate / organic lithium coated silicon-carbon composite material, wherein: the organic lithium compound described in step S4 is one of lithium trifluoromethylsulfonate, lithium methanesulfonate, lithium tetrafluoroborate, lithium p-toluenesulfonate or lithium perfluorobutylsulfonate; the organic solvent is one of methyl formate, ethyl acetate, propyl acetate, isopropyl acetate, butyl acetate or isobutyl acetate.
[0012] Compared with the prior art, the present invention has obvious beneficial effects. From the above technical scheme, it can be seen that the composite material of the present invention is a core-shell structure, the middle layer of lithium silicate improves the lithium ion conductivity, and the outer shell is an organic lithium compound that has good compatibility with the electrolyte and can improve the initial efficiency. The present invention introduces silane gas into amino porous carbon to deposit nano-silicon, obtains a nitrogen-doped silicon-carbon precursor material, and improves the electronic conductivity of the material; oxidizes its surface to generate silicon oxide-coated silicon-carbon material, and the obtained material reacts with lithium hydride for pre-lithiation to obtain a lithium silicate-coated silicon-carbon composite material, which can reduce expansion and improve the initial efficiency. The organic lithium compound is coated on the lithium silicate-coated silicon-carbon composite material by an atomization method, which has the advantages of uniform coating and high efficiency, and the structure of the coating layer material does not change, which is beneficial to improving the initial efficiency of the material and its cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1This is a SEM image of the lithium silicate / organic lithium-coated silicon-carbon composite material prepared in Example 1. DETAILED DESCRIPTION
[0014] Embodiment 1:
[0015] A method for preparing a lithium silicate / organic lithium coated silicon-carbon composite material comprises the following steps:
[0016] Step S1: adding porous carbon to a fluidized bed, introducing nitrogen to exhaust the air in the cavity, and heating to 900° C., then introducing ammonia gas (flow rate 300 ml / min) for 600 min to obtain amino porous carbon, then stopping the introduction of ammonia gas, cooling to 550° C., introducing monosilane gas at a flow rate of 300 SCCM for 300 min to obtain a silicon-carbon precursor material;
[0017] Step S2: Under an argon inert atmosphere, the silicon-carbon precursor material is transferred to a tube furnace, and then an oxygen mixed gas (oxygen: nitrogen volume ratio = 3:10) is introduced at a flow rate of 100 SCCM for 150 minutes for light passivation to obtain a silicon dioxide-coated silicon-carbon precursor material;
[0018] Step S3: at a dew point of ≤-50° C., 100 g of a silicon dioxide-coated silicon-carbon precursor material and 8 g of lithium oxide were mixed evenly, and heated to 750° C. for 9 hours to obtain a lithium silicate-coated silicon-carbon material;
[0019] Step S4: Add 5 g of lithium trifluoromethanesulfonate to 100 g of methyl formate organic solvent to prepare a mixed organic lithium solution with a mass concentration of 5 wt%; atomize the organic lithium solution into gas by atomization method at a vacuum degree of 50 Pa and a temperature of 80° C., and transfer 100 g of lithium silicate-coated silicon-carbon material to a vacuum furnace for deposition on its surface for 150 min. The obtained material is vacuum dried at 80° C. for 24 h to obtain a lithium silicate / organic lithium-coated silicon-carbon composite material.
[0020] Embodiment 2:
[0021] A method for preparing a lithium silicate / organic lithium coated silicon-carbon composite material comprises the following steps:
[0022] Step S1: adding porous carbon to a fluidized bed, introducing nitrogen to exhaust the air in the cavity, and heating to 800° C., introducing dinitrogen tetrahydride gas (flow rate 300 ml / min) for 600 min to obtain amino porous carbon, then stopping the introduction of dinitrogen tetrahydride gas, cooling to 450° C., introducing disilane gas at a flow rate of 100 SCCM for 600 min to obtain a silicon-carbon precursor material;
[0023] Step S2: Under an argon inert atmosphere, the silicon-carbon precursor material is transferred to a tube furnace, and then an oxygen mixed gas (oxygen: nitrogen volume ratio = 1:10) is introduced at a flow rate of 50 SCCM for 300 minutes for light passivation to obtain a silicon dioxide-coated silicon-carbon precursor material;
[0024] Step S3: at a dew point of ≤-50° C., 100 g of a silicon dioxide-coated silicon-carbon precursor material and 5 g of lithium oxide are mixed evenly, and heated to 700° C. for 12 hours to obtain a lithium silicate-coated silicon-carbon material;
[0025] Step S4: Add 5 g of lithium methanesulfonate to 500 g of ethyl acetate to prepare a mixed organic lithium solution with a mass concentration of 1 wt%; atomize the organic lithium solution into gas by atomization at a vacuum degree of 1 Pa and a temperature of 50°C, and transfer 100 g of lithium silicate-coated silicon-carbon material to a vacuum furnace, deposit it on the surface of the lithium silicate-coated silicon-carbon material for 30 minutes, and dry the obtained material at 80°C in vacuum for 24 hours to obtain a lithium silicate / organic lithium-coated silicon-carbon composite material.
[0026] Embodiment 3:
[0027] A method for preparing a lithium silicate / organic lithium coated silicon-carbon composite material comprises the following steps:
[0028] Step S1: adding porous carbon to a fluidized bed, introducing nitrogen to exhaust the air in the cavity, and heating to 1000° C., introducing dinitrogen tetrahydride gas (flow rate 300 ml / min) for 600 min to obtain amino porous carbon, then stopping the introduction of dinitrogen tetrahydride gas, cooling to 650° C., introducing monosilane gas at a flow rate of 500 SCCM for 60 min to obtain a silicon-carbon precursor material;
[0029] Step S2: Under an argon inert atmosphere, the silicon-carbon precursor material is transferred to a tube furnace, and then an oxygen mixed gas (volume ratio of oxygen: nitrogen = 5:10) is introduced at a flow rate of 200 SCCM for 30 minutes for light passivation to obtain a silicon dioxide-coated silicon-carbon precursor material;
[0030] Step S3: at a dew point of ≤-50° C., 100 g of silicon dioxide-coated silicon carbon precursor material and 10 g of lithium oxide are mixed evenly, and heated to 800° C. for 6 hours to obtain a lithium silicate-coated silicon carbon material;
[0031] Step S4: adding 10g of lithium tetrafluoroborate to 100g of propyl acetate organic solvent to prepare a mixed organic lithium solution with a mass concentration of 10wt%; atomizing the organic lithium solution into gas by atomization method at a vacuum degree of 100Pa and a temperature of 100°C, and transferring 100g of lithium silicate-coated silicon-carbon material to a vacuum furnace, depositing it on the surface of the lithium silicate-coated silicon-carbon material for 300min, and vacuum drying the obtained material at 80°C for 24h to obtain a lithium silicate / organic lithium-coated silicon-carbon composite material.
[0032] Comparative Example 1:
[0033] A method for preparing a silicon-carbon composite material comprises: the difference from Example 1 is that there is no step S2, and the rest is the same as Example 1.
[0034] Comparative Example 2:
[0035] A method for preparing a silicon-carbon composite material comprises: different from Example 1, the lithium silicate-coated silicon-carbon material in step S3 is used as the negative electrode material.
[0036] Test example 1: SEM test
[0037] The lithium silicate / organic lithium coated silicon carbon composite material prepared in Example 1 was subjected to SEM test. The test results are as follows: Figure 1 As shown. Figure 1 It can be seen that the material particles have a granular structure and a reasonable size distribution, and the particle size D50 is between 10-15 μm.
[0038] Test Example 2: Button Battery Test
[0039] The silicon-carbon composite materials obtained in Examples 1-3 and Comparative Examples 1-2 were used as negative electrode materials for lithium-ion batteries and assembled into button-type batteries.
[0040] The specific preparation method is as follows: add a binder, a conductive agent and a solvent to the negative electrode material of a lithium-ion battery, stir and slurry, coat it on a copper foil, and dry and roll it to obtain a negative electrode sheet; the binder used is PVDF, the conductive agent is conductive carbon black (SP), the solvent is N-methylpyrrolidone (NMP), and the amount ratio of the negative electrode material, SP, PVDF, and NMP is 95g:1g:4g:220mL; LiPF6 is the electrolyte in the electrolyte, and a mixture of EC and DEC with a volume ratio of 1:1 is the solvent; the metal lithium sheet is the counter electrode, and the diaphragm is a polypropylene (PP) film. The button cell is assembled in an argon-filled glove box. The electrochemical performance is carried out on a Wuhan Blue Electric CT2001A battery tester, with a charge and discharge voltage range of 0.005V-2.0V and a charge and discharge rate of 0.1C. At the same time, its rate (1C / 0.1C) is tested, and the test results are shown in Table 1.
[0041] At the same time, the specific surface area of the above negative electrode materials was tested in accordance with the national standard GB / T 38823-2020 "Silicon Carbon", and the diffusion coefficient of the material was tested by GITT, and the powder resistance was tested by a four-probe tester. The test results are shown in Table 1
[0042] Table 1
[0043]
[0044]
[0045] It can be seen from the data in Table 1 that the first efficiency, diffusion coefficient and rate performance of the silicon-carbon composite materials prepared in Examples 1-3 of the present invention are better than those in Comparative Examples 1-2. The reason is that lithium silicate is coated on the surface of the graphite material, which increases the ion diffusion coefficient of the material and reduces the defects of the material, thereby improving the rate performance of the material.
[0046] Test Example 3:
[0047] The silicon-carbon composite materials in Examples 1-3 and Comparative Examples 1-2 were used to prepare negative electrode sheets using ternary materials (Li(Ni 0.6 Co 0.2 Mn 0.2 )O2) is the positive electrode material; LiPF6 is the electrolyte in the electrolyte, and a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) with a volume ratio of 1:1 is the solvent; Celgard 2400 membrane is used as the separator to prepare 5Ah soft-pack batteries, which are marked as C1, C2, C3 and D1, D2.
[0048] 3.1 Liquid absorption capacity and electrode surface resistance test
[0049] (1) Liquid absorption capacity test
[0050] Use a 1mL burette and draw VmL of electrolyte, add a drop on the surface of the electrode, and time it until the electrolyte is completely absorbed. Record the time t. The test results are shown in Table 2.
[0051] (2) Electrode surface resistance test
[0052] Use a film resistance tester to test the negative electrode (size 100cm 2 ) A resistance test was performed with a pressure of 50KN, and the surface resistance of the electrode was calculated. The test results are shown in Table 2.
[0053] 3.2x performance test
[0054] Rate performance test:
[0055] The charge and discharge voltage range is 2.5~4.2V, the test temperature is 25±3.0℃, and the battery is charged at 1.0C, 2.0C, 3.0C, and 5.0C, and discharged at 1.0C. The constant current ratio and temperature of the battery under different charging modes are tested. The test results are shown in Table 3.
[0056] Table 2
[0057] Group Liquid absorption speed (t) Electrode sheet surface resistance (Ω·cm) Example 1 89 4.32 Example 2 71 5.43 Example 3 98 3.76 Comparative Example 1 112 9.47 Comparative Example 2 45 11.32
[0058] It can be seen from Table 2 that the liquid absorption capacity and surface resistance of the silicon-carbon composite materials obtained in Examples 1-3 are significantly higher than those in the comparative example. The reason is that the materials in the examples have a high specific surface area, which shortens the liquid absorption time and has a low powder resistivity, thereby reducing the surface resistance of the electrode.
[0059] Table 3
[0060]
[0061]
[0062] It can be seen from Table 3 that the rate performance of the battery made of the lithium silicate / organic lithium coated silicon-carbon composite material provided by the present invention is significantly better than that of the comparative example. The reason is that compared with the comparative example, the material of the embodiment is coated with inorganic lithium salt and lithium phosphate on the surface of the material at the same time, which improves the diffusion coefficient of the material and reduces the powder resistivity, improves the constant current ratio under different rate conditions and reduces the temperature rise.
[0063] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A lithium silicate / organic lithium coated silicon carbon composite material, wherein the composite material presents a core-shell structure, wherein the core is a nitrogen-doped silicon carbon material, the middle layer is lithium silicate, and the outer shell is an organic lithium compound; according to the thickness ratio of the composite material, the core: the middle layer: the outer shell = 100: 1-5: 5-15.
2. A method for preparing a lithium silicate / organic lithium coated silicon-carbon composite material, comprising the following steps: Step S1: adding porous carbon to a fluidized bed, introducing nitrogen to exhaust the air in the cavity, heating to 800-1000° C. and then introducing nitrogen source gas to obtain amino porous carbon, stopping introducing nitrogen source gas, cooling to 450-650° C., introducing silane gas at a flow rate of 100-500 SCCM for 60-600 min to obtain a silicon-carbon precursor material; Step S2: under an inert atmosphere, the silicon-carbon precursor material is transferred to a tube furnace, and then an oxygen mixed gas (the volume ratio of oxygen: nitrogen = 1-5:10) is introduced at a flow rate of 50-200 SCCM for 30-300 minutes for light passivation to obtain a silicon dioxide-coated silicon-carbon precursor material; Step S3: according to the mass ratio of silicon dioxide coated silicon carbon precursor material: lithium hydride = 100: 5-10, at a dew point of ≤-50°C, the silicon dioxide coated silicon carbon precursor material and lithium oxide are mixed evenly, and heated to 700-800°C for 6-12h to obtain lithium silicate coated silicon carbon material; Step S4: adding an organic lithium compound to an organic solvent to prepare a uniform organic lithium solution with a mass concentration of 1-10wt%, depositing the organic lithium compound on the surface of the lithium silicate-coated silicon-carbon material at a vacuum degree of 1-100 Pa, a temperature of 50-100° C., and a deposition time of 30-300 min, and vacuum drying at 80° C. for 24 h to obtain a lithium silicate / organic lithium-coated silicon-carbon composite material.
3. A method for preparing a lithium silicate / organic lithium coated silicon-carbon composite material according to claim 1, wherein: The nitrogen source gas in step S1 is one of ammonia or dinitrogen tetrahydrogen.
4. A method for preparing a lithium silicate / organic lithium coated silicon-carbon composite material according to claim 1, wherein: The silane gas in step S1 is one of monosilane or disilane.
5. A method for preparing a lithium silicate / organic lithium coated silicon-carbon composite material according to claim 1, wherein: The organic lithium compound described in step S4 is one of lithium trifluoromethanesulfonate, lithium methanesulfonate, lithium tetrafluoroborate, lithium p-toluenesulfonate or lithium perfluorobutylsulfonate.
6. A method for preparing a lithium silicate / organic lithium coated silicon-carbon composite material according to claim 1, wherein: The organic solvent is one of methyl formate, ethyl acetate, propyl acetate, isopropyl acetate, butyl acetate or isobutyl acetate.
Citation Information
Cited By
Negative active material, preparation method thereof and lithium ion battery
CN119852361A
